Trends in antimicrobial resistance of extended-spectrum beta-lactamase-producing Escherichia coli in urinary tract infections in ICU and non-ICU settings at Ngoerah Hospital, 2020-2022 - Bryan Setiawan; Ni Nyoman Sri Budayanti; Fatmawati, Ni Nengah Dwi; I Putu Bayu Mayura (Journal of Clinical Microbiology and Infectious Diseases, 2025)
Background: Urinary Tract Infection (UTI) is one of the most common nosocomial infections, with Escherichia coli (E. coli) as the primary pathogen. The misuse and overuse of antibiotics has led to the emergence of antibiotic resistance, particularly in Extended-Spectrum Beta-Lactamase (ESBL)-producing E. coli. This resistance presents a significant challenge in managing UTIs, especially among ICU and non-ICU ward patients. This study aims to analyze trends in antibiotic resistance of ESBL-producing E. coli in UTI patients in ICU and non-ICU settings at Ngoerah Hospital during 2020–2022. Methods: A descriptive study with a cross-sectional approach was conducted. The inclusion criteria of this study were samples with identification results of E. coli bacteria with VITEK 2 Compact (bioMérieux, France), which showed E. coli with a probability greater than or equal to 90% and accompanied by sensitivity of E. coli bacteria to antibiotics. Result: Among 789 samples meeting inclusion criteria, 90% (714) were from non-ICU wards, while 10% (75) were from ICU wards. ESBL-producing E. coli accounted for 53% (416), while non-ESBL strains constituted 47% (373). The prevalence of ESBL-producing E. coli in non-ICU wards increased from 43% (96 isolates) in 2020 to 47% (129 isolates) in 2021 and 51% (149 isolates) in 2022. In ICU wards, prevalence rose from 3% (6 isolates) in 2020 to 4% (12 isolates) in 2021 and 8% (24 isolates) in 2022. Tigecycline, meropenem, and ertapenem demonstrated high sensitivity (≥96%), while beta-lactam antibiotics like ampicillin, cefixime, and cefazolin showed 100% resistance. Conclusion: The increasing resistance of ESBL-producing E. coli, particularly in non-ICU settings, highlights the need for strict antibiotic policies and monitoring to prevent further resistance.